2018
DOI: 10.5152/eurjther.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge levels and attitudes of diabetic patients about their disease

Abstract: Objective: Diabetes is a serious health problem worldwide that leads to high morbidity and mortality rates. The current study was conducted to determine the knowledge levels and attitudes of diabetic patients about their disease. Methods: The population of this cross-sectional study comprised type 1 and type 2 diabetic patients who presented to the outpatient internal disease polyclinic of a public hospital. No sampling was done, and 335 diabetic patients who volunteered to participate and were able to communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The questions were developed in the light of literature. In order to prepare the question in regard to this part, “Patients’ knowledge about the disease” in the form of introductory features developed by Karakurt et al ( 14 ) was used and the questions were adapted to children with type 1 diabetes. In addition, the Diabetes Diagnosis and Treatment Guidelines of the Diabetes Foundation of Turkey were reviewed and the items that individuals with type 1 diabetes should know were reached and the questions were finalized in accordance with the guideline ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…The questions were developed in the light of literature. In order to prepare the question in regard to this part, “Patients’ knowledge about the disease” in the form of introductory features developed by Karakurt et al ( 14 ) was used and the questions were adapted to children with type 1 diabetes. In addition, the Diabetes Diagnosis and Treatment Guidelines of the Diabetes Foundation of Turkey were reviewed and the items that individuals with type 1 diabetes should know were reached and the questions were finalized in accordance with the guideline ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…The pineal gland is an endocrine organ adjacent to the posterior wall of the third ventricle between the posterior and dorsal habenular commissures, accounting for the melatonin secretion and chronobiology that regulates circadian rhythm (1). Melatonin is a hormone that regulates the sleep/wake cycle.…”
Section: Introductionmentioning
confidence: 99%
“…It has been seen that individuals with a smaller PGV secrete less melatonin (3). It was suggested that "functional parenchymal volume" (FPGV), which excludes cysts and calcification from pineal gland volume, is actually responsible for melatonin secretion (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…The education of diabetic patients about their disease is an integral part of prevention, treatment and care (1). Realistic perceptions about nutrition are important for the control and prevention of complications (2).…”
mentioning
confidence: 99%